The Impact of Cigarette Consumption on Poverty in Pohuwato District - Aissyah Dien Alkadri; Sri Indriyani Dai; Ivan Rahmat Santoso (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to determine the impact of cigarette consumption on poverty levels in Pohuwato Regency by looking at how much influence and the chances of someone who smokes falling into poverty. The data used in this study are secondary data sourced from the results of SUSENAS KOR and KP in March 2021 at the Central Bureau of Statistics using the logit regression analysis method. The logit model aims to find the probability of an individual or household event falling into poverty or not. The analysis results show that the smoking variable has a significant effect with a greater chance of falling into poverty. This means that someone who smokes has a greater chance of falling into poverty than someone who does not smoke. More people who consume cigarettes will increase the likelihood of falling into poverty more than those who do not.